Total Irregular Labelling Of Butterfly and Beneš Network 5-Dimension - Edy Saputra; Nurdin Hinding; Supri Amir (Jurnal Matematika, Statistika dan Komputasi, 2020)
This paper aims to determine the total vertex irregularity strength and total edge irregularity strength of Butterfly and Beneš Network 5-Dimension. The determination of the total vertex irregularity strength and the edge irregularity strength was conducted by determining the lower bound and upper bound.  The lower bound was analyzed based on characteristics of the graph and other proponent theorems, while upper bound was analyzed by constructing the function of the irregular total labeling. The result show that the total vertex irregularity strength of Butterfly Network , the total edge irregularity strength . The total vertex irregularity strength of Beneš Network , the total edge irregularity strength